Homeland security in the UK: future preparedness for terrorist attack since 9/11 - Wilkinson, Paul F.; Wilkinson, Paul F. (Cass series Political violence, 2007)
'Homeland Security in the UK' examines, especially in the UK context, whether homeland security is striking an appropriate balance. It assesses the nature of responses by key public and private sector bodies in the UK post September 11 for preventing, pre-empting, countering and managing terrorist attack